Empirical Validation of the Relationship between Sustainable Involvement and Family Purchase Behavior (Global Journal of Management and Business Research, 2018)
The present research aims to explain how sustainable involvement can influence the behavior of Algerian families for the purchase of a new car. The main hypothesis of this study was tested on a sample of 210 families. The data obtained were analyzed using structural equation models. The principal results that emerged from this investigation show that the identification of the cognitive and/or emotional purchase process, adopted by family members, could be a relevant avenue for companies to develop and enhance their products. The findings obtained could offer an opportunity to create strong and durable brands.
Keywords: Family structure; Decision-making process; Sustainable involvement